Critical examination of internationalisation: a case study of a collaboration between an Australian and a Chinese university. Issue 1 (2nd January 2018) - Ng, Josephine; Nyland, Berenice
ABSTRACT: In this paper, a case study of an international partnership between two universities, one in Australia and the other in China, is presented. The internationalisation of early childhood degree programmes in Australia is reasonably new and there is limited literature on the subject. This study evaluates a Sino- Australian partnership of a joint undergraduate early childhood programme which is the first of its kind to gain formal accreditation in both Australia and China. The aim of the research was to investigate the challenges of international education initiatives, this model in particular and draw implications for sustainability. A political economy view has framed the research. The study focuses on the perspectives of key players in the joint partnership and in this paper we report from the perspective of senior university staff. The research was designed as a single case study to gain an understanding of the vested interests, intentions and challenges faced in this collaboration. The interplay of the international context, market-forces and transnational activities of internationalised teacher education are highlighted. Findings suggest that the present political environment and changing rules within the international education market makes responsive and collaborative planning difficult to sustain.